THE ELEMENTS OF SUSTAINABLE DEVELOPMENT: PRINCIPLES OF IN-TEGRATION AND SUSTAINABLE UTILIZATION - Andri G. Wibisana (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2014)
Sustainable development is development that meets the needs of the present without compromising the ability of future generations. However, that concept lacks of clarity, which leads to various interpretations. Scholars have argued that the definition of sustainable development can be explained into four elements, namely the integration principle, sustainable use, intra-generational equity, and inter-generational equity. It analyses the elements of integration and sustainable using both legal and non-legal perspectives and shows how the elements have been recognized in various legal documents, while finds that various international commitments have indicated the growing concerns for conservation and sustainable use of natural resources. Pembangunan berkelanjutan adalah pembangunan untuk memenuhi kebutuhan generasi sekarang tanpa mengganggu kemampuan generasi yang akan datang. Definisi pembangunan berkelanjutan dibagi menjadi 4 (empat), yaitu prinsip integrasi, pemanfaatan secara berkelanjutan, keadilan intra generasi, dan keadilan antar generasi. Artikel ini menganalisis prinsip integrasi dan pemanfaatan berkelanjutan. Artikel ini memandang bahwa prinsip integrasi harus diinterpretasikan dalam kerangka perlindungan lingkungan, sehingga memperoleh prioritas guna menyeimbangkan antara kebutuhan perlindungan lingkungan dengan kebutuhan akan pembangunan. Di samping itu, meskipun terdapat berbagai penafsiran mengenai pemanfaatan berkelanjutan, namun pengakuan tentang pemanfaatan berkelanjutan cukup untuk menunjukkan adanya peningkatan perhatian terhadap pemanfaatan berkelanjutan atas sumber daya lingkungan.